The future of Malay–Chinese relations in Malaysia - Mohd. Noor, Noraini (Springer, 2009)
In this chapter, the Malay–Chinese relation is examined by considering the history and nature of the relationship, the ensuing intergroup conflict, and the steps taken by the government and civil society groups to address the conflict. Finally, a psychocultural approach to building peace between the two groups is proposed.